Legal Responsibility For Perpetrators Of Online Gambling Crimes - Beben Bentara; Iskandar Iskandar; Erwin Setianingrat; Deni Yusup Permana; Diky Dikrurahman (Riviera Publishing, 2025)
The rapid expansion of online gambling crimes in Indonesia poses significant legal and social challenges, as existing laws struggle to effectively regulate and prosecute offenders in this evolving digital landscape. Despite regulations under the Criminal Code and the Electronic Information and Transactions (ITE) Law, gaps remain in addressing jurisdictional complexities, inconsistent penalties, and enforcement difficulties. This study aims to identify the legal foundations for prosecuting online gambling crimes, assess the forms of legal liability, and evaluate law enforcement effectiveness in handling such cases. Employing a normative juridical approach, the research analyzes relevant laws, literature, and legal cases. The findings reveal that law enforcement efforts are hampered by inadequate technical regulations, difficulties tracking perpetrators across jurisdictions, and low public awareness of online gambling’s harmful impacts. The study highlights the crucial need for stronger legal frameworks, enhanced law enforcement capacity, and coordinated efforts among government agencies, law enforcement, and internet service providers. It also recommends public education campaigns to increase awareness of the risks and legal consequences of online gambling. These measures are expected to improve the efficacy and comprehensiveness of combating online gambling crimes in Indonesia, safeguarding public morality and social stability in the digital era.